The Academic Performance Stages of Change Inventory (APSCI): An application of the Transtheoretical Model to academic performance - Moreira, Paulo (2021)
The Transtheoretical Model (TTM) conceptualizes change as a process with five identifiable stages. Each stage has psychological characteristics that are manifestations of an underlying continuum of change. Surprisingly few studies have applied the TTM to understand the process involved with academic development. The objective of this study was to assess a new instrument designed to measure the stages of change in the development of academic performance: the Academic Performance Stages of Change Inventory (APSCI). High-school students (N = 564) were sampled from the 10th, 11th, and 12th grades of a secondary school in Portugal. Results showed that a correlated five-factor structure, corresponding to the five stages of change, had good empirical fit. The latent factors of this model (stages) were shown to have the same meaning across school grade and gender. We concluded that the five APSCI subscales had reasonable internal consistency considering the small number of items per factor. Students in the later stages of change tended to have better academic performances and to be more engaged in school than those in the earlier stages, particularly the pre-contemplation stage. This study provides good preliminary evidence that the APSCI is a suitable tool for assessing stages of change of academic performance.